2020
DOI: 10.2174/1570161118666200318104434
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Markers in Cardiovascular Disease; Lessons Learned and Future Perspectives

Abstract: Background: Cardiovascular disease (CVD) still remains the leading cause of morbidity and mortality worldwide. It is now established that inflammation plays a crucial role in atherosclerosis and atherothrombosis, and thus, it is closely linked to cardiovascular disease. Objective: The aim of the present review is to summarize and critically appraise the most relevant evidence regarding the potential use of inflammatory markers in the field of CVD. Method: We conducted a comprehensive research of the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 215 publications
0
7
0
Order By: Relevance
“…Inflammatory cytokines are previously reported to be overexpressed in cerebro‐cardiovascular disease patients. 22 For instance, TNF‐α and IL‐17 are elevated in CHD patients and AIS patients, respectively. 23 , 24 In line with previous studies, it was observed that pro‐inflammatory cytokines TNF‐α, IL‐1β, IL‐6, and IL‐17A were elevated in CHD patients compared to HCs since pro‐inflammatory cytokines heavily participated in atherosclerotic plaque formation and CHD pathogenesis, thus led to CHD occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory cytokines are previously reported to be overexpressed in cerebro‐cardiovascular disease patients. 22 For instance, TNF‐α and IL‐17 are elevated in CHD patients and AIS patients, respectively. 23 , 24 In line with previous studies, it was observed that pro‐inflammatory cytokines TNF‐α, IL‐1β, IL‐6, and IL‐17A were elevated in CHD patients compared to HCs since pro‐inflammatory cytokines heavily participated in atherosclerotic plaque formation and CHD pathogenesis, thus led to CHD occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines are previously reported to be overexpressed in cerebro‐cardiovascular disease patients 22 . For instance, TNF‐α and IL‐17 are elevated in CHD patients and AIS patients, respectively 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a progressive increase in oxLDL levels during nilotinib treatment, but not during imatinib or dasatinib. The combination of inflammatory and oxidative mechanisms that are closely related in atherogenesis and atherothrombotic complications (22,23), may eventually be responsible for nilotinib-associated endothelial activation and the consequent expression of pro-atherogenic adhesion molecules (10) with effects on macrophages and increased LOX-1 expression by these same cells (24). LOX-1, then, mediates oxLDL accumulation in the intima with atherosclerotic plaque growth but it also increases transcription and activity of proteases, responsible for plaque instability and rupture (25)(26)(27)(28) In addition to the pathogenetic aspect, the relevance of the link between inflammatory mechanisms and lipid oxidation is also demonstrated by the reduction of clinical events as evidenced by the outcome of recent intervention trials where a specific anti-inflammatory therapy has been associated with statin treatment (29).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that changes in peripheral blood composition, which reflect the inflammatory condition of the human body, have prognostic value for various diseases, including cardiac diseases. 12 The systemic immune-inflammation index (SII) and systemic inflammation-response index (SIRI), which are calculated based on peripheral blood count values, are two novel biomarkers that might provide additional information that traditional risk factors cannot provide. 13 These biomarkers have been found to be related to increased risk of stroke and all-cause mortality in the general population.…”
Section: Introductionmentioning
confidence: 99%